A Correlation Between Adolescents’ Knowledge And Attitudes Towards Reproductive Health And Premarital Sexual Behavior At SMK Negeri 3 Bengkulu City - Lidya Oktari; Fikitri Marya Sari; Yusran Fauzi (Student Scientific Journal, 2026)
Based on the data recorded by the World Health Organization (WHO) in 2022, the level of sexual behavior is very high in both developing and developed areas. 9.3% or approximately 3.7 million adolescents reported having engaged in sexual intercourse. According to KPAI (2022), sexual behavior among adolescents in 38 provinces in Indonesia, based on survey results, reports that 62.7% of Senior High School (SMA) students are not virgins, 22.6% of adolescents have had sexual relations, 97% have watched pornography, and 21.26% have undergone abortions. The purpose of this study is to determine the relationship between adolescents' knowledge and attitudes towards reproductive health and premarital sexual behavior at SMK Negeri 3, Bengkulu City. The method used is a quantitative approach with a cross-sectional study design. This research was conducted at SMK Negeri 3, Bengkulu City, with the population taken from the XI Broadcasting, XI Beauty, and XII Beauty classes. The data were collected by distributing questionnaires to 75 respondents. The results of univariate analysis showed that the majority of respondents (62.7%) had good knowledge, the majority of respondents (57.3%) had negative attitudes, and the majority of respondents (53.3%) had poor premarital sexual behavior. The results of bivariate analysis indicated a significant relationship between adolescents' knowledge and premarital sexual behavior with a p-value of 0.015, and a relationship between adolescents' attitudes and premarital sexual behavior with a p-value of 0.033. The researchers recommend that the school continue to educate students about reproductive health and the factors that may influence premarital sexual behavior among adolescents.